The impact of using artificial intelligence methods on improving the quality of supply services in the government sector: An applied study on the Ministry of Human Resources and Social Development in the Kingdom of Saudi Arabia - Alshehri, Wesam Ghareeb; Abdallah, Sumia Ibrahim Ahmad (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to determine the impact of using artificial intelligence methods on improving the quality of supply services in the government sector, as well as identifying the proposed mechanisms for developing the use of artificial intelligence in the Ministry of Human Resources and Social Development. The study relied on the analytical descriptive approach, and the study population consisted of employees working in the Ministry of Human Resources and Social Development, and the researcher distributed the study tool electronically to the members of the study population. (100) employees working in the Ministry responded to the distribution process. The results of the study showed that there is agreement among the study individuals on the impact of artificial intelligence with its various applications (expert systems, artificial neural networks, genetic algorithms, fuzzy logic systems) on the quality of supply services within the Ministry, and that there is a medium degree of agreement among the study individuals on Obstacles and problems that negatively affect the quality of procurement services within the Ministry. The results of the study also showed that there is strong agreement among the study individuals on the proposed mechanisms for developing the use of artificial intelligence in the Ministry. Also, the results of the study showed that there is a statistically significant relationship between the use of artificial intelligence applications and the improvement of supply services in the Ministry. In light of the findings, the researcher recommends the following: (The need to hold workshops on an ongoing basis to solve emergency work problems and to increase interaction with workers- Work to provide material and moral incentives to the employees of the organization that encourages them to use modern and innovative applications that help them to complete their work).